Prevalence of oral tori and exostosis in Malaysian population - A cross-sectional study - Ashish Kumar Singh; Srinivas Sulugodu Ramachandra; Shelly Arora; Daniel Devaprakash Dicksit; C.G. Kalyan; Priyanshi Singh (Elsevier, 2017)
Introduction: Oral tori and exostosis are non-pathological bony protuberances seen on the alveolar surfaces of the jaw bones. These are commonly seen on the palatal surfaces of the maxilla [torus palatinus (TP)] and around the premolars in the lingual surface of the mandible [torus mandibularis (TM)]. The aim of this cross-sectional study was to determine the prevalence of tori/exostosis in the Malaysian population. Methodology: A total of 2666 patients were examined for the presence of tori and exostosis in the maxilla and mandible and were categorized into TP, TM, and exostosis (facial/labial). Collected data was analysed for obtaining descriptive statistics. Results: 882 subjects were noticed with oral tori/exostosis among the population studied with a prevalence rate of 33%. TP was seen more in females (35%), compared to males (20%), and this difference was statistically significant (p value < 0.001). Highest prevalence of TP was seen in Malays (43%), followed by Chinese (31%) and Indians (21%), which was statistically significant (p value < 0.00). Discussion: High prevalence of tori and exostosis was seen in the population studied. Though harmless, in certain circumstances, their presence necessitates changes in the denture design during fabrication of prosthesis, which the dentist should be mindful.